Structural equation modelling of teachers’ perspectives on microlearning in Saudi EFL instruction: examining predictors of adoption and implementation - Mohammad Hamad Al-khresheh; Rim Al Basheer Ben Ali; Mayez Almayez; Shatha Fahad Alruwaili; Aisha Fadl Almola Mohammed Alimam (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract Microlearning, with its potential to deliver focused, engaging, and learner-centred instruction, has become an innovative strategy in English as a foreign language (EFL) instruction. However, its practical implementation in Saudi classrooms remains underexplored, particularly from the teachers’ perspective. This study investigated the relationships among familiarity with microlearning, perceived benefits, challenges, and recommendations for its integration into EFL instruction. Employing a quantitative research design, data were collected from 248 EFL teachers selected using stratified sampling to ensure diverse representations across gender, age, teaching experience, and institutional type. The study utilized a validated questionnaire to gather insights, with data analyzed using structural equation modelling. The findings revealed that familiarity with microlearning significantly enhanced perceived benefits (β = 0.93, p < 0.01) and reduced perceived challenges (β = − 0.68, p < 0.01). Perceived benefits positively influenced recommendations for adoption (β = 0.48, p < 0.01), whereas challenges negatively impacted recommendations (β = − 0.32, p < 0.01). Moderating effects demonstrated that teaching experience strengthened the relationship between familiarity and perceived benefits, whereas institution type influenced how challenges affected recommendations. Based on these findings, implications are suggested to support the effective integration of microlearning into Saudi EFL classrooms. These include implementing targeted teacher training programs to enhance familiarity with microlearning strategies, investing in technological infrastructure to address practical challenges, and developing institution-specific support systems to ensure equitable access to resources.